(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article explores the role of digital platforms and ecosystems in ensuring macroeconomic stability and increasing youth employment. The study analyzes Uzbekistan’s opportunities at the stage of the demographic dividend and structural imbalances in the traditional labor market. The multiplicative effect of digital ecosystems in addressing the problem of “skills mismatch” in the digital economy is substantiated. The paper concludes with proposals for institutional regulation and macroeconomic stimulation of digital youth employment.